HUBUNGAN INTENSITAS PENGGUNAAN SITUS JEJARING SOSIAL (SJS) TERHADAP INFORMASI KEISLAMAN - Arwendria Arwendria; Gusnar Zain; Randa Erdianti (Jurnal IPI (Ikatan Pustakawan Indonesia), 2017)
The purpose of this study was to examine the correlation between the intensity using social networking sites (SJS) and student motivation on the credibility of Islamic information published on Facebook. This study consists of two variables, namely the independent variable (X) is the intensity of the use of SJS by IAIN students Imam Bonjol, Padang and the dependent variable (Y) is the student's motivation on the credibility of Islamic information contained in Facebook. Sampling is done by using purposive random sampling. The sample that will be taken in this research is IAIN Imam Bonjol students, whose curriculum offers more Islamic studies as many as 210 students. The results showed that the higher the intensity of use of Facebook, the higher the validity of the media according to users. Through the mastery of these skills, students are not just social media users, especially Facebook, but also can be a source of referrals for other social media users against Islamic information. For curriculum development policy-makers it is time to include (embedded) literacy skills in all curricula in each study program at IAIN Imam Bonjol.